Extraction, Characterization and Optimization of High Ester Pectin from Mango Fruit (Mangifera indica) Waste Using (3)2 Factorial Design - Malviya, Rishabha; T. Kulkarni, Giriraj; Malaviya, Tanya (Current Nutrition & Food Science, 2015)
A (3)2-factorial design was employed to optimize extraction of high ester pectin using two independent variables (extraction time and temperature) from mango fruit waste i.e. its peels. Citric acid solution (0.5 molar) was used to acidify water at pH 2. Using a new methodology waste management was done by extracting pectin from peels obtained from local juice shops. It was then characterized as pharmaceutical excipient. Combined effects of independent variables on degree of esterification (DE) were investigated and % deviation from predicted response was calculated. The model built for DE shows that both variables have significant effect on response and temperature of extraction medium which has a negative effect on DE. 3-D surface response showed relationship of independent variables on DE. Results showed that batch F4 deviated 10.83% from predicted response and had maximum D.E. (68.97%), followed by F7 which had value of 63.64% with relatively less deviation (0.99%).
Keywords: extraction